Systematic Review: Comprehensive Methods for Detecting BRCA1 and BRCA2 Mutations in Breast and Ovarian Cancer - Lucky, Muhammad Haris; Baig, Saeeda; Hanif, Muhammad; H Asghar, Asghar (Asian Pacific Journal of Cancer Biology, 2025)
This review explores various methods for detecting BRCA1 and BRCA2 mutations, including Array Comparative Genomic Hybridization (aCGH), Denaturing High-Performance Liquid Chromatography (DHPLC), Digital PCR, High-Resolution Melting Analysis (HRMA), Multiple Ligation-dependent Probe Amplification (MLPA), Next-Generation Sequencing (NGS) & NGS-panels, RNA methods, and Sanger Sequencing. The search used articles published between 2018 and 2023, focusing on genetic testing for BRCA mutations and techniques for identifying these mutations. The review identifies the advantages and limitations of each method, such as Sanger sequencing is more advantageous for large-scale genotyping than targeted deep sequencing. NGS is a high-throughput platform that requires bioinformatics support and is more useful than Sanger sequencing. Both MLPA and aCGH are useful in detecting LGRs and cannot be substituted by DNA sequencing. PCR-based methods like HRMA are fast and relatively cheap, while DHPLC is cheap and efficient due to its mutation sensitivity and specificity. Digital PCR and RNA-based methods have higher accuracy and precision, with increased detection sensitivity. New technologies such as CRISPR- based diagnostics and third-generation sequencing (ONT) shows a lot of potential. The decision on which detection method to use, depends on the type, variety, scale, and costs of mutation typing necessary in clinical or research scenarios. One example is using one network with multiple algorithms, which offers full results in the shortest time possible. The main focus of this review is to identify the strengths, limitations and cost of each method in detecting BRCA1/2 mutations.